An HPLC evaluation of the vitamin B12 and folate synthesis by the Propionibacterium freudenreichii group - Van Wyk, Jessy (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhDVoedselwet) -- University of Stellenbosch, 2002.